Effect of fly ash particle reinfo rcement on microstructure, porosity and hardness in Al-(Si-Mg) cast composites - M.B. Harun; S.R. Shamsudin; H. Yazid; Z. Selamat; M.S. Sattar; M. Jalil (Universitas Gadjah Mada, 2006)
The microstructure of cast Al-4Si-Mg reinforcedwith fly ash particles at various particlecontents has been studied. The composites were fabricated by stir casting process andcharacterized by optical microscopy, image analyzer, scanning electron microscopy and hardness measurements. The results showed that particle contents affected to the presence oforosities and hardness of the composites. It was observed that increasing the fly ash contentincrease the porosity in the composites, with the matrix alloy reinforced with 15 wt.% of fly ash particles having the highest porosity and lowest hardness.